Mitigasi Risiko Kepailitan Klub Liga 1 Indonesia: Implementasi Sport Corporate Legal Coaching Framework Pada Sistem Lisensi PSSI - Jantarda Mauli Hutagalung (Bulletin of Community Engagement, 2025)
This study analyzes the implications of club licensing regulations established by the Football Association of Indonesia on the bankruptcy risk of clubs participating in Liga 1 Indonesia, using a legal coaching approach as an instrument of preventive law. Club licensing regulations generally emphasize administrative and financial compliance; however, their effectiveness in mitigating bankruptcy risk remains limited due to the lack of systematic integration of internal legal risk management. This research adopts a normative juridical and conceptual approach, employing a legal model-building technique. The findings indicate that club licensing in Indonesia remains largely verificative in nature and has not yet functioned as a mechanism of risk governance. Accordingly, this article formulates the Sport Corporate Legal Coaching Framework (SCLCF) as an integrative model that combines licensing regulations with an internalized legal risk management system. The primary contribution of this study lies in integrating corporate law into professional sport governance, while also providing a learning framework for club managers, regulators, and academics to develop sustainable and resilient sport governance systems against bankruptcy risk